The influence of inductive activities on pupils' conceptualization and attitudes to the greenhouse effect and climate change - Kováčová, Lucia; Held, Ľubomír; Kotuľáková, Katarína (International research in geographical and environmental education, 2025)
The greenhouse effect poses a significant environmental challenge to humanity today. Research shows that many students lack adequate knowledge about this phenomenon. To address this issue, we have developed educational materials that utilize various instructional approaches to improve primary school students' understanding and attitudes toward the greenhouse effect. This material is designed to make environmental topics accessible within the formal education system. We assessed the students' understanding of the greenhouse effect using a three-level test and their subjective attitudes toward climate change using a semantic differential. Additionally, we employed The Climate Change Attitude Survey to evaluate their attitudes toward environmental problems, with a focus on climate change. Overall, the results indicate that incorporating a sequence of activities based on the designed educational materials into the school curriculum has a positive impact on students' understanding and attitudes toward the greenhouse effect.